(untitled) (Journal of Humanities and Social Sciences Research, 2023)
Physiotherapy is a medical profession and an important branch of medicine, through which trained professionals evaluate and treat physical dysfunction associated with an injury, disability, disease or health condition. Whereas, physiotherapy sessions may be a stand-alone option for treating various diseases, or it may be as a kind of auxiliary treatment that is prescribed in addition to other treatments. Their motor function is threatened by age, injuries, disease, movement disorders, or other environmental factors. Here, this research discusses the concept of physiotherapy, its most important types, techniques, treatment methods, and its most important effects on the rehabilitation of athletes.